Ketamine Boluses Are Associated with a Reduction in Intracranial Pressure and an Increase in Cerebral Perfusion Pressure: A Retrospective Observational Study of Patients with Severe Traumatic Brain Injury - Bradley A. Dengler; Oliver Karam; Colleen A. Barthol; Aaron Chance; Laura E. Snider; Clare M. Mundy; Michael T. Bounajem; William C. Johnson; Moustafa M. Maita; Paola M. Mendez-Gomez; Ali Seifi; Shaheryar Hafeez (Critical Care Research and Practice)
Background. Increased intracranial pressure (ICP) and hypotension have long been shown to lead to worse outcomes in the severe traumatic brain injury (TBI) population. Adequate sedation is a fundamental principle in TBI care, and ketamine is an attractive option for sedation since it does not commonly cause systemic hypotension, whereas most other sedative medications do. We evaluated the effects of ketamine boluses on both ICP and cerebral perfusion pressure (CPP) in patients with severe TBI and refractory ICP. Methods. We conducted a retrospective review of all patients admitted to the neurointensive care unit at a single tertiary referral center who had a severe traumatic brain injury with indwelling intracranial pressure monitors. We identified those patients with refractory intracranial pressure who received boluses of ketamine. We defined refractory as any sustained ICP greater than 20 mmHg after the patient was adequately sedated, serum Na was at goal, and CO2 was maintained between 35 and 40 mmHg. The primary outcome was a reduction in ICP with a subsequent increase in CPP. Results. The patient cohort consisted of 44 patients with a median age of 30 years and a median presenting Glasgow Coma Scale (GCS) of 5. The median reduction in ICP after administration of a ketamine bolus was −3.5 mmHg (IQR −9 to +1), and the postketamine ICP was significantly different from baseline (p<0.001). Ketamine boluses led to an increase in CPP by 2 mmHg (IQR −5 to +12), which was also significantly different from baseline (p<0.001). Conclusion. In this single-institution study of patients with severe traumatic brain injury, ketamine boluses were associated with a reduction in ICP and an increase in CPP. This was a retrospective review of 43 patients and is therefore limited in nature, but further randomized controlled trials should be performed to confirm the findings.